Adenoid basal carcinoma of the uterine cervix: a case report - Tan, Yuan; Lai, Liqin (Frontiers in Oncology, 2026)
BackgroundAdenoid basal carcinoma (ABC) is a rare human papillomavirus (HPV)-related malignancy of the uterine cervix that predominantly affects postmenopausal women, and it is a low-grade tumor with a favorable prognosis. This report presents a case of ABC along with a detailed immunohistochemical analysis.Case presentationA 65-year-old woman tested positive for HPV types 16, 35, and 56 during routine screening. A subsequent cervical biopsy indicated adenocarcinoma. The patient was asymptomatic. She underwent radical hysterectomy, bilateral salpingo-oophorectomy, and bilateral pelvic lymph node dissection. A comprehensive pathological examination of the hysterectomy specimen confirmed ABC with a focal component of high-grade squamous intraepithelial lesion (HSIL). The postoperative course was uneventful, and no recurrence or metastasis was observed during 4 years of follow-up.ConclusionAdequate tissue sampling and appropriate immunohistochemical profiling are valuable for accurate diagnosis and differentiation of ABC from other malignant cervical lesions.